Deciphering ankle dynamics: EEG BCI-robotic system to predict continuous ankle joint movements in passive, active, and imagined training - Tong, Grace Min (Nanyang Technological University, 2024)
Background: The rehabilitation of ankle-joint movements, specifically dorsiflexion and plantarflexion, is crucial for individuals suffering from motor disabilities and neural limitations due to ageing, strokes, and locked-in syndrome (LIS). These conditions often result in foot drop, significantly impairing individuals’ daily activities and quality of life. The integration of Electroencephalogram (EEG) with robotic devices presents a novel approach to enhancing rehabilitation training, leveraging the advancements in BCI and robotics.